Identification of copy number variations associated with congenital heart disease by chromosomal microarray analysis and next‐generation sequencing. (8th March 2016) - Zhu, Xiangyu; Li, Jie; Ru, Tong; Wang, Yaping; Xu, Yan; Yang, Ying; Wu, Xing; Cram, David S.; Hu, Yali
Abstract: Objective: To determine the type and frequency of pathogenic chromosomal abnormalities in fetuses diagnosed with congenital heart disease (CHD) using chromosomal microarray analysis (CMA) and validate next‐generation sequencing as an alternative diagnostic method. Method: Chromosomal aneuploidies and submicroscopic copy number variations (CNVs) were identified in amniocytes DNA samples from CHD fetuses using high‐resolution CMA and copy number variation sequencing (CNV‐Seq). Result: Overall, 21 of 115 CHD fetuses (18.3%) referred for CMA had a pathogenic chromosomal anomaly. In six of 73 fetuses (8.2%) with an isolated CHD, CMA identified two cases of DiGeorge syndrome, and one case each of 1q21.1 microdeletion, 16p11.2 microdeletion and Angelman/Prader Willi syndromes, and 22q11.21 microduplication syndrome. In 12 of 42 fetuses (28.6%) with CHD and additional structural abnormalities, CMA identified eight whole or partial trisomies (19.0%), five CNVs (11.9%) associated with DiGeorge, Wolf‐Hirschhorn, Miller‐Dieker, Cri du Chat and Blepharophimosis, Ptosis, and Epicanthus Inversus syndromes and four other rare pathogenic CNVs (9.5%). Overall, there was a 100% diagnostic concordance between CMA and CNV‐Seq for detecting all 21 pathogenic chromosomal abnormalities associated with CHD. Conclusion: CMA and CNV‐Seq are reliable and accurate prenatal techniques for identifying pathogenic fetal chromosomal abnormalities associated with cardiac defects. © 2016 John Wiley & Sons, Ltd. Abstract : What's Already Known About This Topic? CNVs play an important role in the pathogenesis of CHD. CMA is the gold standard for CNV detection. NGS is a newly developed method for genome‐wide CNV detection. What Does This Study Add? When CHD is complicated with other malformations, chromosomal abnormalities are detected as frequently as submicroscopic CNVs. NGS is an alternative method to CMA with similar sensitivity and specificity.